Development of Academic Transcript Management Information System - Budi Nugroho; Yisti Vita Via (Nusantara Science and Technology Proceedings)
The academic transcripts management system in UPN "Veteran" of East Java is currently arranged based on the courses that have been taken by students who are sorted alphabetically. The problem is there is no information about the courses in each semester, so the academic transcript can not be used to know the progress of student learning. It also can not know whether there is a course that has not been taken in the previous semesters, because it can affect the process of taking courses in the next semester related to the rules of the prerequisite course. The system also lists all the courses that have been taken by the student although re-taking the course. Thus, grade point average/GPA on the Transcript is actually less valid, since the calculation of GPA should only be based on the course with the best score (when the student repeats the same course). In addition, how to know which courses have graduated and not graduated must be done through manual examination. These problems are currently done manually, which is certainly very inefficient. In this study, the application system was developed to manage the Academic Transcripts (Information System of Academic Transcripts Management). In this system, courses of old curriculum will be converted to new curriculum courses. Transcript only include graduated courses, classified per semester on the current Curriculum. The system is also designed to provide information on what courses have been taken and which have not. With this new system, the management of Academic Transcripts can be done more effectively and efficiently, thereby reducing errors and abuse intentionally or unintentionally. This certainly supports the performance of academic supervision by leaders at the level of study program, faculty, and university.